Uma análise dos atos de assédio moral contra as docentes da esfera pública municipal de João Pessoa frente ao contexto social, político e educacional - Santos, Priscila Morgana Galdino dos (2021)
This paper is a case study conducted among teachers who work for the João Pessoa City Council and sought to understand the following question: How have female Basic Education teachers in the city of João Pessoa experienced acts of bullying by their peers or immediate bosses? Therefore, our General Objective was based on the following assertion: to analyze the practices of acts of bullying against female teachers in the João Pessoa Municipal School and how they understand the consequences of these practices in their professional and personal lives. To conduct this qualitative research, we sought the testimony of 20 female teachers from the Municipal Government of João Pessoa, who were heard through semi-structured interviews conducted by Google Meet in the year 2021. For data analysis, we followed the steps of Bardin's Content Analysis (2016). We found the veiled and public presence of Bullying and even Sexual Harassment against the female teachers, considering the high degree of consequences that such acts brought on the personal and professional lives of each one, although the female teachers exercised practices of defense and resistance, resignifying the work spaces and the profession itself. They also experienced serious consequences in the health sphere. As a thesis, we present that the professional space of the municipal teaching staff of João Pessoa has, in the practices of moral harassment, the perpetuation of power, contradicting the perspective of a humanizing education. Thus, it is presented as urgent the strengthening of the policy of prevention of acts of moral harassment in the Municipal Education of João Pessoa.